2022
DOI: 10.3389/fnmol.2022.992494
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonication effects on graphene composites in neural cell cultures

Abstract: Spinal cord injuries and neurodegenerative diseases, including Parkinson’s, Alzheimer’s, and traumatic brain injuries, remain challenging to treat. Nowadays, neural stem cell therapies excite high expectations within academia. The increasing demand for innovative solutions in regenerative medicine has drawn considerable attention to graphene materials. Due to unique properties, carbon materials are increasingly used as cellular scaffolds. They provide a biological microenvironment supporting cell adhesion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…There may be a mechanism by which graphene was capable of transmitting electrical stimulation signals and stimulating neuronal differentiation and extension. A recent study found that graphene substrates as cell scaffolds with appropriate electrical stimulation can dramatically increase the number of cells [ 6 ]. Supporting cell adhesion and promoting cell proliferation were the main mechanisms by which graphene substrates work [ 99 ], showing great potential in regenerative medicine.…”
Section: Application Of 2d Materials In Neural Repair and Synaptic Si...mentioning
confidence: 99%
See 3 more Smart Citations
“…There may be a mechanism by which graphene was capable of transmitting electrical stimulation signals and stimulating neuronal differentiation and extension. A recent study found that graphene substrates as cell scaffolds with appropriate electrical stimulation can dramatically increase the number of cells [ 6 ]. Supporting cell adhesion and promoting cell proliferation were the main mechanisms by which graphene substrates work [ 99 ], showing great potential in regenerative medicine.…”
Section: Application Of 2d Materials In Neural Repair and Synaptic Si...mentioning
confidence: 99%
“…GBNs can also induce the behavior of neural cells. Graphene substrates have been shown to support neural cell adhesion, which in turn promotes cell reproduction [ 6 ]. Similarly, Wang et al found that the number of nerve regeneration factors secreted by neural cells cultured on silk-graphene hybrid hydrogel was significantly increased, and the axon length and proportion of cells also increased slightly [ 104 ].…”
Section: Application Of 2d Materials In Neural Repair and Synaptic Si...mentioning
confidence: 99%
See 2 more Smart Citations
“…Dybowska-Sarapuk et al demonstrated that using GBNs as cellular scaffolds to electrostimulate mouse NE-4C neural stem cells promoted their suitable development. 97 Fang et al focused on the metabolomics of neural stem cells (NCSs) induced by culturing on 3DG foam. The authors established a correlation between metabolic reconfiguration and the proliferation rate of NSCs on a different scaffold.…”
Section: Gene and Cell Therapiesmentioning
confidence: 99%